(untitled) (Global Journal of Medical Research, 2015)
This article innovatively elaborates on two entirely useful and harmful angles of science education in building growing economy nationally and globally. Static economy-demolishing schooling versus accountable and moral economy-flourishing mentorship is delineated from a science edification philosophy. Generating moral figures and perceptions from scientific and educational discoveries must be globally pursued. This is key to maintaining an expanding nature for science-founded economy and to establishing national and international peace and prosperity.